A cataract surgery barrier model in Malaysia - Abdul Mutalib, O.; Asma', H.; Nurulain, M.Z; Ahmad Shahir, A.M. (2018)
Cataract is a serious public health problem as the most common cause of blindness. Timely cataract surgery is required to prevent visual loss. Our ‘Cataract Surgery Barrier Model’ illustrates the barrier in accessing cataract surgery services in Malaysia. Issues include their perceived need for sight, apprehension, physical status, family support, financial adversity, nondisclosure of their visual problems, belated needs for better sight, social stigma, miscommunication and delayed referral. Factors at the specialist level are accessibility, bureaucracy, waiting time and cost. This model is designed to elucidate the effect of delayed presentation, detection, and referral procedure on the timing for cataract surgery.